Serum Uric Acid and Hyperuricemia Associate with Coronary Artery Disease among Postmenopausal Women - Qianyun Guo; Yang Liu; Xunxun Feng; Jiaqi Yang; Guangyao Zhai; Yujie Zhou (Reviews in Cardiovascular Medicine, 2022)
Background: Serum uric acid (SUA) levels has been considered a possible risk factor for coronary artery disease (CAD) for many years. Since SUA levels are greatly affected by medications, diet, and metabolism, the association between SUA and CAD has been controversial for centuries. While, the state of hyperuricemia (HUA) has been proven to have a negative impact on CAD in previous studies, there are still few clinical and epidemiological studies of HUA in CAD. In particular, evidence of this association is limited in postmenopausal women. This study explored the influence of SUA levels and HUA on CAD in this demographic group. Methods: In total, 5435 postmenopausal women were allocated to either a non-CAD group (n = 2021) or a CAD group (n = 3414). Regression analyses, including generalized linear models (GLM), correlation analysis, comparison between stratified groups, and analysis by use of diuretics were carried out on data obtained in this study. Results: SUA and HUA were found to associate significantly with CAD by univariate logistic regression analysis. In addition, GLM showed nonlinear response of CAD probability with increasing level of SUA. In multivariate analysis, we found that SUA and HUA were independently related to CAD. Correlation analysis showed that SUA and HUA both correlated positively with CAD (p < 0.001). By comparing the stratified age groups, we found that the differences among the age groups were significant (p < 0.05). Conclusions: SUA and HUA were shown to be independently associated with CAD among postmenopausal women.